Carcinoid tumors of the appendix - Bentancor, Marisel; Villariño, Alicia; Pereyra Núñez, Diego (Cirugía del Uruguay, 2006)
Appendicular tumors have low incidence and are the most frequent (up to 85% of neoplasias affecting this location). In general, this condition is detected only when the specimen removed from a patient operated from acute appendicitis is sent in for analysis. Therefore surgeons should bear in mind the importance of sending the specimen removed to the anatomopathology laboratory. In this case there new case have been reported, and conduct upon finding said tumor is discussed in the paper